Analisis Pengaruh Kualitas Produk dan Harga terhadap Keputusan Pembelian Smartphone: (Studi Kasus Mahasiswa IAIN Syekh Nurjati Cirebon) - Arifudin Arifudin; Delina Delina; Salma Nabila; Putri Ramadhan Lestari; Ika Josi Fiana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to analyze the effect of product quality and price on the decision of smartphone purchase. A purchase decision is a process that consumers go through to choose and buy a product or service to meet their needs and desires. High product quality and good at affordable prices are the main factors that drive consumers to buy a product by considering the quality and price ratio in making decisions at the time of purchase. Consumer satisfaction in product quality is very important in maintaining the existence of a company or business unit makes an understanding of digital marketing, product quality and service quality cannot be seen low. The population in this study were smartphone consumers from among IAIN students Syekh Nurjati Cirebon, determining the number of samples by spreading questionnaires and sample 55 people obtained. The data collection techniques through this questionnaire have been carried out validity tests, rallies and classical assumptions. This research method uses multiple linear regression analysis. From the results of this study, the results were obtained that partially shows the quality of the product had a positive and significant effect on the purchase decision, then the price of a positive and significant effect on the purchase decision. While simultaneously or along with the quality of the product and the price affects the smartphone purchase decision. The study provides implications for smartphone manufacturers to improve product quality and offer competitive prices to increase the smartphone purchase decision by IAIN students Syekh Nurjati Cirebon.